2020
DOI: 10.1089/thy.2019.0688
|View full text |Cite
|
Sign up to set email alerts
|

Patient Age Is an Independent Risk Factor of Relapse of Differentiated Thyroid Carcinoma and Improves the Performance of the American Thyroid Association Stratification System

Abstract: Background: The 2015 American Thyroid Association (ATA) guidelines proposed a three-category system for estimating the risk of recurrence of differentiated thyroid carcinoma (DTC). This system includes several perioperative features, but not age at diagnosis. However, age has traditionally been recognized as a critical factor in the survival of DTC patients, and the eighth edition of TNM stated that patients older than 55 years were at higher risk of death. In this study, we raised the question of whether age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 15 publications
0
26
2
Order By: Relevance
“…Interestingly, age > 55 years was not significantly associated with a higher risk for disease. This is in contrast to a prior study by Trimboli et al [ 27 ], who showed that high-risk patients (as stratified by ATA criteria [ 28 ]) older than 55 years had the highest risk for relapse and significantly shorter disease-free survival. A possible explanation is the assumably small number of high-risk patients, as patients with tumors showing macroscopic ETE were not included, and the generally smaller sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, age > 55 years was not significantly associated with a higher risk for disease. This is in contrast to a prior study by Trimboli et al [ 27 ], who showed that high-risk patients (as stratified by ATA criteria [ 28 ]) older than 55 years had the highest risk for relapse and significantly shorter disease-free survival. A possible explanation is the assumably small number of high-risk patients, as patients with tumors showing macroscopic ETE were not included, and the generally smaller sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, the ATA IRSS was designed to stratify the DTC patients according to the risk of tumor progression, instead of the death of the disease 3,8 . As the relationship between the events is unquestionable, 3,11,12 TNM has also been frequently used in clinical practice to assess the risk of cancer recurrence and to guide treatment and follow‐up 11 …”
Section: Discussionmentioning
confidence: 99%
“…Relapses, in turn, affect survival with mortality rates reaching more than 10% if locoregional disease and if an incomplete response to additional treatment is found, 9 escalating to 55% with the development of distant metastases 3,10 . Therefore, disease‐free survival (DFS) has been considered a better predictor of outcome than overall survival (OS), as the death of the disease can actually happen decades after the tumor diagnosis 11,12 . In clinical practice, nonetheless, the applicability of TNM system for recurrence prediction has been suggested 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…Old age is a risk factor for poor prognosis of PTC patients [15,20] and a recent AJCC TNM staging system used a 55-years cutoff to upstage patients. Whereas Jeon et al [21] reported that patients aged ≥45 years were at a higher risk of LNM; other studies revealed that young people are also more likely to have LNM [22].…”
Section: Discussionmentioning
confidence: 99%